2022
DOI: 10.3389/fpsyt.2022.827981
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sphingosine-1-Phosphate Receptor-1 Protein Expression in the Dorsolateral Prefrontal Cortex Between Schizophrenia Type 1 and Type 2

Abstract: Understanding the etiology and treatment approaches in schizophrenia is challenged in part by the heterogeneity of this disorder. One encouraging progress is the growing evidence that there are subtypes of schizophrenia. Recent in vitro findings of messenger ribonucleic acid (mRNA) gene expression on postmortem dorsolateral prefrontal cortex (DLPFC) showed that schizophrenia has two subtypes, those with a relatively normal DLPFC transcriptome (Type 1) and those with differentially expressed genes (Type 2). Sph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Interestingly, it was shown that the protein encoded by S1PR1 can be accessed via positron emission tomography (PET) in vivo using specific radioligands. Both the mRNA and the S1PR1 protein levels were found to be up-regulated in schizophrenia "Type 2," and it was suggested as a future imaging biomarker to distinguish between schizophrenia "Type 1" and "Type 2" subgroups (Chand et al, 2022), that were mentioned above (Bowen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was shown that the protein encoded by S1PR1 can be accessed via positron emission tomography (PET) in vivo using specific radioligands. Both the mRNA and the S1PR1 protein levels were found to be up-regulated in schizophrenia "Type 2," and it was suggested as a future imaging biomarker to distinguish between schizophrenia "Type 1" and "Type 2" subgroups (Chand et al, 2022), that were mentioned above (Bowen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent targeted mass spectrometry-based analysis found that postmortem samples of the corpus callosum of patients with SZ have lower levels of S1P ( 268 ). Furthermore, one study divided patients with SZ into those that present an upregulation of S1PR1 and those that have levels comparable to controls ( 269 ). This may be used as a biomarker since S1PR1 can be detected through positron emission tomography ( 269 ).…”
Section: Role Of Gpcrs In Cellular Signaling In Szmentioning
confidence: 99%
“…Furthermore, one study divided patients with SZ into those that present an upregulation of S1PR1 and those that have levels comparable to controls ( 269 ). This may be used as a biomarker since S1PR1 can be detected through positron emission tomography ( 269 ).…”
Section: Role Of Gpcrs In Cellular Signaling In Szmentioning
confidence: 99%
“…In the central nervous system (CNS), S1PR1 is expressed in neurons, astrocytes, microglia, and oligodendrocytes and plays an important role in neural development and neuroinflammatory processes . Recent studies have demonstrated that S1PR1 is involved in several CNS disorders including multiple sclerosis (MS), traumatic brain injuries, neuropathic pain, and schizophrenia …”
Section: Introductionmentioning
confidence: 99%